Agaricus and the Theme of “Death” - Leupen, Alex (Homœopathic Links, 2013)
Alex Leupen has worked in the Homeopathic Doctorsʼ Centre in Utrecht, The Netherlands, since 1990. Eight colleagues work in this centre, including Jan Scholten. Alex is an experienced teacher on the underlying systems in the plant families and the periodic table of the elements pertaining to homeopathic practice. In this column he shares clinical tips.
Keywords: Kingdoms; Fungi; Agaricus muscarius; Amanita muscaria; Death; Tics